2022
DOI: 10.3390/rs14030479
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Inter-Comparison of Multi-Source High Spatial Resolution Evapotranspiration Products over Lancang–Mekong River Basin, Southeast Asia

Abstract: Evapotranspiration (ET) plays a crucial role in water balance within the global hydrological cycle. Timely assessment of ET products can provide the scientific basis for quantitative analysis of hydrological cycle processes and water resources assessment. In this paper, four high spatial resolution remote sensing ET products—the Moderate-resolution Imaging Spectroradiometer global terrestrial evapotranspiration product (MOD16), the ET product based on Penman–Monteith–Leuning equation version 2 (PML-V2), the ET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Studies such as Hu and Mo 123 and Chen et al . 124 have evaluated the performance of these products in the MRB and found that their accuracy can vary depending on specific conditions and characteristics of the region. Chen et al .…”
Section: Methodsmentioning
confidence: 99%
“…Studies such as Hu and Mo 123 and Chen et al . 124 have evaluated the performance of these products in the MRB and found that their accuracy can vary depending on specific conditions and characteristics of the region. Chen et al .…”
Section: Methodsmentioning
confidence: 99%
“…The sources and use of LAI in these two products are also different. LAI is used to increase leaf conductance in MOD16, while it is used to divide the total available energy into canopy uptake and soil uptake in PMLv2 (Mu et al, 2011;Zhang et al, 2019;Chen et al, 2022).…”
Section: Comparison Of Steep Model Estimates With Global Evapotranspi...mentioning
confidence: 99%
“…MOD16 requires air temperature, atmospheric pressure, relative humidity, and downward shortwave radiation. In addition to these elements, PMLv2 also requires precipitation, downward longwave radiation, and wind speed (Mu et al, 2011;Zhang et al, 2019;Yin et al, 2020;Chen et al, 2022). Although both ET products use the same land cover data (MOD12Q1), only MOD16 integrates it into its algorithm.…”
Section: Comparison Of Steep Model Estimates With Global Evapotranspi...mentioning
confidence: 99%
“…Although both ET products use the same land cover data (MOD12Q1), only MOD16 integrates it into its algorithm. In MOD16, the land cover type defines biome delimitation for the characterization of leaf stomatal conductance, vapour pressure deficit (VPD) and other related factors, while PMLv2 only uses land cover to construct a mask of the land area (Chen et al, 2022). The sources and use of LAI in these two products are also different.…”
Section: Comparison Of Steep Model Estimates With Global Evapotranspi...mentioning
confidence: 99%
See 1 more Smart Citation